Taking Stock : Who Benefited from the Oil Price Shocks? - Cerdeiro, Diego (IMF Working Papers; Working Paper ;, 2017)
The effect that the recent decline in the price of oil has had on growth is far from clear, with many observers at odds to explain why it does not seem to have provided a significant boost to the world economy. This paper aims to address this puzzle by providing a systematic analysis of the effect of oil price shocks on growth for 72 countries comprising 92.8% of world GDP. We find that, on net, shocks driving the oil price in 2015 shaved off 0.2 percentage points of growth for the median country in our sample, and 0.17 percentage points in GDP-weighted terms. While increases in oil supply and shocks to oil-specific demand actually boosted growth in 2015 (by about 0.2 and 0.4 percentage points, respectively), weak global demand more than offset these gains, reducing growth by 0.8 percentage points. Counterfactual simulations for the 72 countries in our sample underscore the importance of diversification, rather than low levels of openness, in shielding against negative shocks to the world economy.